Legal Analysis of The Role of Mediators in The Sibolga Religious Court in Minimizing Divorce Rates - Chairun Nabila; Syofiaty Lubis (Journal Equity of Law and Governance, 2024)
This study aims to analyze the role of mediators in the mediation process of divorce cases at the Sibolga Religious Court and the effectiveness of mediation efforts in minimizing the divorce rate. Based on data from the Sibolga Religious Court, there was a significant increase in the success rate of mediation in 2021 and 2022. In 2021, from a target mediation success rate of 5%, the realization reached 11.36%, more than double the initial target. In 2022, the success of mediation increased again, reaching 20%, aligning with the set target. In addition, the number of divorce cases decreased from 142 cases in 2021 to 127 cases in 2022. This type of research uses qualitative research with data collection techniques through in-depth interviews with mediators and direct observation to the Sibolga Religious Court and relies on legal documents, mediation reports, related laws and regulations, journals, books, and other relevant articles. The results of the study show that mediators have an important role in facilitating communication and negotiation between the parties to the case, helping them reach a peaceful agreement without having to proceed with the divorce. The increase in mediation effectiveness can be attributed to a variety of factors, including mediator training, a more personalized approach, and increased public awareness of the importance of mediation. In conclusion, mediation at the Sibolga Religious Court has proven to be effective in reducing the divorce rate, and with a more intensive strategy, mediation has greater potential to resolve family conflicts.